Virginia impartially examined, and left to publick view, to be considered by all iudicious and honest men. Under which title, is comprehended the degrees from 34 to 39, wherein lyes the rich and healthfull countries of Roanock, the now plantations of Virginia and Mary-land. Looke not upon this booke, as those that are set out by private men, for private ends; for being read, you'l find, the publick good is the authors onely aime. For this piece is no other then the adventurers or planters faithfull steward, disposing the adventure for the best advantage, advising people of all degrees, from the highest master, to the meanest servant, how suddenly to raise their fortunes. Peruse the table, and you shall finde the way plainely layd downe. / By William Bullock, Gent. [electronic resource] :
Summary goes here